2006
DOI: 10.1017/s1138741600006089
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological Symptoms, Social Skills, and Personality Traits: A Study with Adolescents

Abstract: The purpose of this study is two-fold: (a) to study the concomitant relationships between psychopathological symptoms, cooperation, social skills, and other personality traits; and (b) to identify the predictive variables of psychopathological symptoms. The sample consists of 322 adolescents aged 14 to 17 years old. This study uses correlational methodology. In order to assess psychopathological symptoms, cooperation, social skills, and personality traits, the following scales are used: the Symptom Checklist (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 32 publications
1
9
0
4
Order By: Relevance
“…Following a group of adolescents over a 6 years period Pelkonen et al (2003) found that baseline low selfesteem scores were predictive of depression. Likewise, adolescents with identifiable levels of psychopathology are characterized by low level of social skills such as inappropriate assertiveness (Landazabal 2006). Chan (1993) with Chinese university undergraduates found nonassertive responses to correlate with depression.…”
Section: Introductionmentioning
confidence: 99%
“…Following a group of adolescents over a 6 years period Pelkonen et al (2003) found that baseline low selfesteem scores were predictive of depression. Likewise, adolescents with identifiable levels of psychopathology are characterized by low level of social skills such as inappropriate assertiveness (Landazabal 2006). Chan (1993) with Chinese university undergraduates found nonassertive responses to correlate with depression.…”
Section: Introductionmentioning
confidence: 99%
“…La popularidad y el estatus sociométrico en el grupo de iguales se ha estudiado en relación con el ajuste psicosocial (Garaigordobil, 2006), el ajuste escolar (Martín, 2011) y las atribuciones académicas. En este sentido, la mayoría de las investigaciones se centran en la forma en que los estudiantes interpretan el rechazo que pueden estar sufriendo y las atribuciones de causalidad que realizan sobre su situación.…”
Section: Tipos Sociométricos Y Autoatribuciones Académicasunclassified
“…Popularity and sociometric status in the peer group have been studied in relation to psychosocial adjustment (Garaigordobil, 2006), scholastic adjustment (Martín, 2011) and academic attributions. Most of this research focuses on the way that students interpret the rejection they may be suffering, and the causality attributions that they make about their situation.…”
Section: Sociometric Types and Academic Self-attributionsmentioning
confidence: 99%